Phenomenological Study of the Implementation of Digitalization in the Management of Medical Hazardous Waste - Adli, Shofa Samiroh; Andry, Andry; Pamungkas, Rian Adi; Karnando, Joni (Universitas Negeri Padang, 2024)
This study aims to describe the process of implementing digitalization in the management of hazardous medical waste (B3 waste) at RSIA Siti Hawa Padang. The sub-focus of this research includes providing an overview of the application of Festronik, a description of the Festronik usage process, an overview of the benefits of using Festronik, and an overview of the management of hazardous medical waste and its environmental impact. The research method employed is qualitative, exploring the phenomenon in-depth. Data were obtained through interviews with 10 informants, comprising 2 primary informants and 8 key informants from RSIA Siti Hawa Padang. Sample selection was carried out using purposive sampling to ensure a comprehensive understanding. Data analysis in this study used Collaizi's nine-step data interpretation method (1978). The findings of this research reveal a comprehensive understanding of the general implementation of digitalization through Festronik at RSIA Siti Hawa Padang. The application of Festronik enhances the effectiveness of hazardous medical waste management, improves hospital accreditation assessments, and effective hazardous medical waste management has a positive impact on the hospital's environmental health.